Significance of beach geomorphology on fecal indicator bacteria levels. Issue 1 (15th August 2017) - Donahue, Allison; Feng, Zhixuan; Kelly, Elizabeth; Reniers, Ad; Solo-Gabriele, Helena M.
Abstract: Large databases of fecal indicator bacteria (FIB) measurements are available for coastal waters. With the assistance of satellite imagery, we illustrated the power of assessing data for many sites by evaluating beach features such as geomorphology, distance from rivers and canals, presence of piers and causeways, and degree of urbanization coupled with the enterococci FIB database for the state of Florida. We found that beach geomorphology was the primary characteristic associated with enterococci levels that exceeded regulatory guidelines. Beaches in close proximity to marshes or within bays had higher enterococci exceedances in comparison to open coast beaches. For open coast beaches, greater enterococci exceedances were associated with nearby rivers and higher levels of urbanization. Piers and causeways had a minimal contribution, as their effect was often overwhelmed by beach geomorphology. Results can be used to understand the potential causes of elevated enterococci levels and to promote public health. Abstract : Graphical highlights Highlights: Enterococci percent exceedance levels were compared to beach characteristics. Beach geomorphology was the primary feature associated with exceedances. Marsh and bay beaches were characterized by higher enterococci exceedances. Statistical analysis using large database and satellite imagery is useful to identify factors that influence water quality.